Ochratoxin A Control in Meat Derivatives: Intraspecific Biocompetition between Penicillium nordicum Strains. (11th January 2017) - Berni, Elettra; Montagna, Irene; Restivo, Francesco Maria; Degola, Francesca
Abstract : A Penicillium nordicum strain previously assessed for its atoxigenicity was tested against a toxigenic strain of the same species on salami, in order to assess its effectiveness as a biocontrol agent for OTA containment. Sixty salami were inoculated with different combinations of P. nordicum OTA−/OTA+ suspensions and ripened under controlled thermohygrometric conditions. After 7, 18, 29, and 40 days, both fungal counts and chemical analyses were carried out on casings. OTA was never found in salami used as a control, while it was occasionally detected in traces (0.08–0.76 μ g/kg) in salami inoculated with the atoxigenic P. nordicum strain. It was otherwise detected at levels varying from 2.84 to 15.85 μ g/kg in coinoculated salami and from 48.66 to 177.79 μ g/kg in salami inoculated with the toxigenic P. nordicum strain. OTA levels detected when coinoculation occurred were 91.1%, 85.8%, and 94.2% lower than those found in samples inoculated with the toxigenic strain, respectively, after 18, 29, and 40 ripening days. Biocontrol approach using intraspecific competition proved very effective in reducing both settlement of toxigenic strains and OTA contamination and could be therefore considered an interesting strategy to avoid OTA contamination in moulded meats, if used in association with fungal commercial starters.